1996
DOI: 10.1111/j.1476-5381.1996.tb15298.x
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester activation of chloride current in guinea‐pig ventricular myocytes

Abstract: 1 Although earlier studies with phorbol esters indicate that protein kinase C (PKC) may be an important regulator of Cl-current (Icl) in cardiac cells, there is a need for additional quantitative data and investigation of conflicting findings. Our objectives were to measure the magnitude, time course, and concentration-dependence of Ic, activated in guinea-pig ventricular myocytes by phorbol 12-myristate 13-acetate (PMA), evaluate its PKC dependence, and examine its modification by external and internal ions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 64 publications
2
17
1
Order By: Relevance
“…Recent studies (Chan et al, 1995 ;Koumi et al, 1995 ;Shuba et al, 1996) utilizing either the shortcircuit current or the patch clamp technique demonstrated that the PMA stimulated Cl − current in a dosedependent manner. Our observed transient stimulation of I sc induced by PMA (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies (Chan et al, 1995 ;Koumi et al, 1995 ;Shuba et al, 1996) utilizing either the shortcircuit current or the patch clamp technique demonstrated that the PMA stimulated Cl − current in a dosedependent manner. Our observed transient stimulation of I sc induced by PMA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another type of Cl − channel, which is modulated either directly or indirectly by Ca# + , has been observed in rat lacrimal gland acinar cells (Evans and Marty, 1986), T84 cells (Cliff and Frizzell, 1989), and human airway epithelial cells (Frizzell, Rechkemmer and Shoemaker, 1986). Moreover, PKC-modulated Cl − transport has been reported in rat corneal epithelial cells (Crosson et al, 1986), rat epididymal epithelial cells (Chan, Hon and Wong, 1995), guinea pig ventricular myocytes (Shuba, Asai and McDonald, 1996), and guinea pig hepatocytes (Koumi, Sato and Aramaki, 1995). The purpose of the present study was to investigate whether Cl − secretion in the pigmented rabbit conjunctiva was modulated by intracellular Ca# + and PKC in addition to cAMP.…”
Section: Introductionmentioning
confidence: 96%
“…Hunter, 1995) (Matsuura & Ehara, 1992;Kaneda et al, 1994;Walsh & Long, 1994;Shuba et al, 1996a), the magnitude of the activation is far smaller than that observed with stimulation of the cyclic AMP pathway (e.g. Shuba et al, 1996a) (Tsunoda et al, 1993) or 3T3 cells (Illek et al, 1995), and Akiyama & Ogawara (1991) reported that 370 yM GST had no effect on phosphodiesterase activity under in vitro conditions. While these findings suggest that GST did not activate Ic by elevating cyclic AMP in the myocytes investigated here, there is a need for more direct evidence on this point.…”
Section: Involvement Of Tyrosine Phosphorylationmentioning
confidence: 99%
“…Pipettes were pulled from thickwalled borosilicate glass capillaries (Jencons, Bedfordshire, U.K.) in the usual two-step process (Hamill et al, 1981 supplied in the dialysate (cf. Tseng, 1992;Vandenberg et al, 1994;Shuba et al, 1996b (Bahinski et al, 1989;Harvey & Hume, 1989;Walsh & Long, 1994;Zhang et al, 1994;Shuba et al, 1996a).…”
Section: Cell Isolationmentioning
confidence: 99%
“…A Cl -channel conductance is activated by angiotensin II via AT 1 receptors in sinoatrial cells 13 and by adenosine in guinea pig ventricular myocytes, 14 whereas activation of angiotensin II AT 1 receptors 15 and adenosine A 1 /A 3 receptors 16,17 is thought to trigger IP. In addition, transient exposure to phorbol 12-myristate 13-acetate, which has been shown to mimic the protection of IP via protein kinase C (PKC) activation in isolated cardiomyocytes, 18 activates a Cl -current in feline 19 and guinea pig ventricular myocytes 20 but not in rabbit atrial myocytes. 6 It is noteworthy that a transient increase in [Ca 2ϩ ] i resulting from Ca 2ϩ entry during the initial preconditioning ischemia is thought to mediate the protection of IP by triggering the activation of PKC 21 and to activate a Ca 2ϩ -dependent Cl -conductance in rabbit ventricular myocytes.…”
Section: ͼImentioning
confidence: 99%